Effect of alternating salinity stress on the gut microbiota of razor clam Sinonovacula constricta - Yuan, Yi; Jiang, Qunqun; Xue, Qinggang; Lin, Zhihua; Dai, Wenfang (Frontiers in Marine Science, 2024)
Introduction Razor clam (Sinonovacula constricta) is a bivalve of economic importance that widely resides in coastal and estuarine areas where salinity fluctuates rapidly. Gut microbiota, which plays a pivotal role in the disease resistance against pathogens and the growth and development of aquatic animals, is affected by salinityfluctuation in ambient environment. However, there is limited knowledge about the underlying mechanism of how clam gut microbiota respond to alternating salinity stress. Methods Here, we exposed S. constricta to different salinity treatments including normal salinity-acclimated (NN, 20 psu), low salinity-acclimated (LL, 5 psu), low salinity-stressed (NL, transferred from 20 to 5 psu) and normal salinity-stressed (LN, transferred from 5 to 20 psu) groups. The former two groups were used as the control, and the latter two groups aimed to investigate the effect of alternating salinity stress on clam growth and gut microbiota by 16S rRNA gene amplicon sequencing. Results Alternating salinity stress caused faster and higher mortality compared with the two control groups, and disrupted the gut microbiota including altered α-diversity, composition and structure. The salinity stress, hours post stress and their interaction had significant impact on the gut microbiota, which contributed 4.5%, 9.5% and 6.0%, respectively, to the variance in the gut communities. Alternating salinity stress increased the proportion of stochastic processes in governing the gut microbiota to a certain extent, and the stochasticity aggravated with the increase of stress time. Furthermore, the gut bacterial interspecies interaction networks exhibited more complex and higher connected topology in two alternating salinity stress groups compared with the control group (NN), and the interaction relationships between core OTUs in gut networks were altered after salinity stress. The functional potentials involved in immune system and metabolisms of amino acid, energy, carbohydrate and lipid remarkably increased in LN and NN groups after salinity exposure for 96 h compared to corresponding 0 h, while these pathways exhibited the opposite pattern in NL and LL groups. Discussion Collectively, our findings provide evidence that alternating salinity stress has potentially negative effect on the growth of S. constricta from an ecological viewpoint.